2023
DOI: 10.3390/nu15071649
|View full text |Cite
|
Sign up to set email alerts
|

Is Maternal Carbohydrate Intake Having an Impact on Newborn Birth Weight? A Systematic Review

Abstract: Glucose is a vital fuel for fetal growth, and carbohydrates are the primary source of glucose in the diet. The effects of carbohydrate intake during pregnancy on neonatal birth weight have not been fully investigated or systematically reviewed. Therefore, this systematic review aimed to collate the available evidence to determine whether carbohydrate intake during pregnancy impacts newborn birth weight. A literature search was performed from inception to March 2022 in Embase, Medline, and PsycInfo. Articles pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 33 publications
0
0
0
Order By: Relevance
“…The pregnant women in the present study had a lower energy intake (1623.87 ± 494.08 Kcal/day) than in the study of pregnant women conducted in the UK (2329 [1882, 2789] kcal/day) examining carbohydrate intake (302.7 [245.7, 372.9] g/day) [40]. The proportion of energy from carbohydrates was higher in our study cohort (56%) than in Western populations (47.3% to 51%) but similar to a Japanese cohort (55.3%) [16] The proportion of total protein (15.46 ± 2.68%) was within the recommended proportion (25%) [41]. As there were relatively minor effects of protein and fat intake on fetal growth in our study cohort, further research should focus on the sources and quality of carbohydrates and their association with pregnancy gut microbiota compositions and diversity to modulate and improve pregnancy health and birth outcomes.…”
Section: Discussionsupporting
confidence: 44%
See 3 more Smart Citations
“…The pregnant women in the present study had a lower energy intake (1623.87 ± 494.08 Kcal/day) than in the study of pregnant women conducted in the UK (2329 [1882, 2789] kcal/day) examining carbohydrate intake (302.7 [245.7, 372.9] g/day) [40]. The proportion of energy from carbohydrates was higher in our study cohort (56%) than in Western populations (47.3% to 51%) but similar to a Japanese cohort (55.3%) [16] The proportion of total protein (15.46 ± 2.68%) was within the recommended proportion (25%) [41]. As there were relatively minor effects of protein and fat intake on fetal growth in our study cohort, further research should focus on the sources and quality of carbohydrates and their association with pregnancy gut microbiota compositions and diversity to modulate and improve pregnancy health and birth outcomes.…”
Section: Discussionsupporting
confidence: 44%
“…Despite carbohydrates being a primary energy source for fetuses, a systematic review including 86,461 maternal-child pairs found minimal impact of maternal carbohydrate intake on neonatal birth weight [16]. While some studies reported positive relationships between neonatal birth weight and carbohydrate intake, most studies showed no significant association [16].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations